Comparison of winning points and penalties between different weight categories for female cadets in judo - Kajmovic, H.; Becic, F. (Sportski Logos, 2021)
The aim of this research is the comparison of winning points (Ippon and Waza-ari) and penalties (Shido), which were the reason for the victory in judo fight between different weight categories for female cadets. The sample consisted of 1459 winning points and 163 penalties between eight different weight categories for female cadets in judo. Variables for this research are winning points Ippon and Waza-ari and penalty Shido. The data were collected from official competition reports for each weight category from European, World and EYOF competitions from 2017 - 2019 year. The results from Pearson's Chi-square test showed the existence of tatistically significant differences (p=.05) between weight categories for female cadets. The variable that contributes most to this difference is the Waza-ari point in the + 70kg weight category. The results of this research can contribute to the improvement of cadets training practice and new ways of researching this issue at different age categories of both genders. Key words: